Survival And Penetration Of Salmonella Spp. Inoculated On Washed And Unwashed Eggshell Stored At Different Temperatures - Tan, Jie Yi (Universiti Sains Malaysia, 2021)
Egg washing and storage temperature are the key factors at influencing Salmonella contamination on egg surface and content over a period of storage. In the present study, experiment explored the effect of washing and storage temperatures on the survival and penetration ability of Salmonella on the eggshell and into the egg content stored at 1, 5, 7, 15, 22, and 28 days. Tap water and dish sponge were used to mimic the household washing practice. Salmonella concentration at approximately 8 log CFU/mL was inoculated on egg surface with whole egg penetration method. Salmonella enumeration was carried out on the surface of eggshell, crushed eggshell and egg content. The study indicated that overall survival of Salmonella declined after 28 days of incubation at 4°C and 25°C for washed and unwashed eggs. A significant higher Salmonella survival was observed on the washed (P < 0.05) and unwashed (P < 0.05) eggshell surface at 4°C than 25°C on 28 days of incubation. After 1 day of incubation, the highest reduction of Salmonella (1.31 log CFU/mL) was observed on washed eggs incubated at 25oC. Egg content were tested for the presence and absence of Salmonella. There were 22.22% (8/36 washed eggs) and 8.33% (3/36 unwashed eggs) of egg contents were detected with Salmonella throughout 28 days of incubation. However, all the washed and unwashed eggs stored at 4°C was tested Salmonella negative in content at any time point. This study emphasize egg washing do not give a significant impact to the survival of Salmonella in eggshell and content. Storage temperature at 4°C showed potential inhibition toward the penetration of Salmonella in to the egg content. This finding had reflected on the food safety issue whereby the penetration risk of Salmonella into the egg content can be reduced.